Faktor Pendukung Motivasi Berperilaku Disiplin Pada Santri Pondok Pesantren - Safiruddin Al Baqi; Abdul Latip A; Tyas Sarli Dwiyoga (Educan : Jurnal Pendidikan Islam, 2017)
Discipline behavior is one of the most important behavior to be taught because it could lead someone to follow the rules. Schools is a strategic environment to teach the discipline behavior. Boarding school education system require students to stay in dormitory and every student should always be discipline and follow the rules. This study aims to determine factors that influence students to be discipline. Data obtained by taking survey to 163 students (male: 95; female: 68) from 4 boarding school. Results of analysis show that there are some factors: 1) external motivation of students indiscipline behavior, 2) internal motivation of students indiscipline behavior, 3) external motivation of students discipline behavior, and 4) internal motivation of students disciplined behavior. So it is expected that the findings of this study can help school administrators to create school environment that capable to make student to be discipline.